Fenomena program Ridwan Hasan dalam pembelajaran MNR pada program “Belajar di Rumah” siswa sekolah dasar - Yuni Setyowati; Sandra Bayu Kurniawan; Peduk Rintayati (Universitas Sebelas Maret, 2021)
The purpose of this research is to describe the MNR method in mathematics learning delivered by Ridwan Hasan in the TVRI program